Coil Embolization of an Aneurysm Associated with an Infraoptic Anterior Cerebral Artery in a Child - Al-Qahtani, Sultan; Tampieri, Donatella; Brassard, Rolland; Sirhan, Denis; Mellanson, Denis (American Journal of Neuroradiology, 2003)
Summary: We report an unusual case of a ruptured aneurysm from an infraoptic anterior cerebral artery in an 11-year-old child. To our knowledge, this is the second such case treated with Guglielmi detachable coils in the pediatric population that has been described in the literature, excluding that of a vein of Galen aneurysm that resulted in remarkable recovery. We conclude that the endovascular technique is a feasible treatment option for children with ruptured cerebral aneurysms, especially when more complex vascular anomalies are present.